2016
DOI: 10.1111/edt.12262
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Dental Injuries in the primary dentition: a 15‐year bibliometric analysis of Dental Traumatology

Abstract: The number of articles on TDI in the primary dentition has increased, but remains low. The evaluation of study designs and topics addressed identified gaps that could contribute to the development of new studies on TDI in the primary dentition, especially cohort studies that evaluate risk factors, prognosis, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 26 publications
1
44
1
7
Order By: Relevance
“…In the second stage, studies that adopted Andreasen's criteria for classifying TDI and that used multivariate analysis were deemed eligible for inclusion in the study. Andreasen's criteria were chosen because they are considered more comprehensive and have already been employed in previous studies . Two researchers (TRCS and MBM) conducted the data extraction from the studies, which included information on authors, publication year, state/city where the study took place, participants (sample size/age range), the prevalence of TDI, and risk factors plus their association or not with TDI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second stage, studies that adopted Andreasen's criteria for classifying TDI and that used multivariate analysis were deemed eligible for inclusion in the study. Andreasen's criteria were chosen because they are considered more comprehensive and have already been employed in previous studies . Two researchers (TRCS and MBM) conducted the data extraction from the studies, which included information on authors, publication year, state/city where the study took place, participants (sample size/age range), the prevalence of TDI, and risk factors plus their association or not with TDI.…”
Section: Methodsmentioning
confidence: 99%
“…According to Feldens et al and Kramer et al, Brazil is considered one of the countries that has produced more research on TDI than many other countries. A number of studies have evaluated the prevalence of, and the risk factors for, TDI .…”
Section: Introductionmentioning
confidence: 99%
“…Yang, Needleman & Niederman 16 conducted a bibliometric analysis of the pediatric dental literature in MEDLINE and found that substantial literature is available in pediatric dentistry on which clinical decisions can be based. Kramer et al 17 undertook a 15-year bibliometric analysis of the journal Dental Traumatology in order to understand the traumatic dental injuries in the primary dentition. Pena-Cristobal 18 studied the 100 most cited articles on oral cancer using the Science Citation Index Expanded tool.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analyses in clinical dentistry have been performed in such areas as pulp regeneration and endodontics, 6 dental trauma, 7 , 8 cleft lip and cleft palate, 9 orthodontics, 10 , 11 oral and maxillofacial surgery, 12 dental implantology, 13 and problem‐based learning 14 . In the health professions, this form of analysis has been published in medical education, 15 dental education, 16 health care simulation education, 17 dry eye, 18 and sports and exercise medicine 19 .…”
mentioning
confidence: 99%
“…The data for these analyses are abstracted from published scholarship, usually focusing on the number of citations, citation density, and journal impact factor, as well as author information such as country, institutional affiliation, co-authorship, and international collaboration. [2][3][4][5] Bibliometric analyses in clinical dentistry have been performed in such areas as pulp regeneration and endodontics, 6 dental trauma, 7,8 cleft lip and cleft palate, 9 orthodontics, 10,11 oral and maxillofacial surgery, 12 dental implantology, 13 and problem-based learning. 14 In the health professions, this form of analysis has been published in medical education, 15 dental education, 16 health care simulation education, 17 dry eye, 18 and sports and exercise medicine.…”
mentioning
confidence: 99%